A polymer, a method for preparing the same, and a fluid loss additive containing the same
Patent Information
- Application Number
- CN202210610324.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-05-31
AI Technical Summary
[0004]现有技术中的钻井用降滤失剂在耐温抗盐能力和环保性能两方面往往不能兼顾,顾此失彼,具有一定的局限性,不能很好地进行广泛推广和现场应用
[0053]本发明针对现有技术中的钻井用降滤失剂在耐温抗盐能力和环保性能两方面往往不能兼顾的问题,提供了一种聚合物、其制备方法及含有其的降滤失剂。本发明提供的聚合物中起到骨架作用的主链结构为改性淀粉,原料易于购买、价格低廉且环保性良好;改性淀粉与烯基酰胺、烯基磺酸盐和酚类化合物反应生成的聚合物,抗盐抗高温能力强,高温高盐环境中的护胶作用显著,仍具有很强的水化能力和抗盐性;采用本发明提供的制备方法由所述聚合物和纳米材料制备的降滤失剂在具有良好的抗盐抗高温性的同时,兼具良好的环保性能,降滤失性良好:可以抗饱和盐水;耐温达180℃;在180℃/16h老化后的API中压滤失量≤15mL;生物降解性值BOD5/CODCr>10%,生物毒性满足环保要求EC50≥30000mg/L,可用于构建高性能环保型水基钻井液体系。故由本发明提供的聚合物进一步制备的降滤失剂适合工业批量生产,在油气钻井施工中具有较好的应用效果,降滤失性能相比于现有技术显著增强。
Smart Images

Figure CN117186306B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of petroleum extraction technology, and particularly relates to a polymer, its preparation method, and a filtration loss reducing agent containing the polymer. Background Technology
[0002] With increasing energy pressures, oil exploration and drilling are becoming increasingly sophisticated, leading to a rise in deep and ultra-deep wells and complex geological environments. This is particularly true for ultra-deep wells, high-temperature wells, high-pressure wells, extended reach wells, and deep-water wells, where the challenges of extraction (excessive torque, tripping difficulties, stuck pipe, low drilling speed, wellbore instability, lost circulation, and formation damage) are mounting. To ensure efficient oil drilling and improve oil and gas recovery, higher demands are being placed on drilling fluid technology at every stage, including drilling and cementing, especially in terms of cost and environmental requirements. This makes drilling fluid technology even more crucial in drilling operations. Overcoming the impact of high salinity and high temperature environments on the effectiveness of filtration reducers and improving their environmental performance remains a challenging problem for drilling workers and a key focus and difficulty in drilling fluid research.
[0003] Currently, drilling fluid treatment agents are developing towards higher temperature and salt resistance as well as environmental friendliness, with natural materials becoming a top priority in drilling fluid research. Deepening reforms to traditional technologies, improving overall cost-effectiveness, and developing new temperature- and salt-resistant, environmentally friendly filtration reducers are key focuses for drilling fluid development. Green, environmentally friendly, and naturally modified materials are crucial for enhancing overall performance and laying the foundation for the development of the oil drilling and production industry.
[0004] Existing drilling fluid loss reducers often cannot simultaneously achieve both temperature and salt resistance and environmental performance, resulting in certain limitations and hindering their widespread promotion and field application. Summary of the Invention
[0005] One aspect of the present invention provides a polymer comprising a main chain monomer unit and a side chain monomer unit; wherein the main chain monomer unit is modified starch, and the side chain monomer unit is an alkenyl amide, an alkenyl sulfonate, or a phenolic compound.
[0006] In one specific embodiment, the mass ratio of the main chain monomer unit to the side chain monomer unit is (15 to 35):(28 to 65); and / or
[0007] The mass ratio of the alkenylamide, alkenyl sulfonate, and phenolic compound is (10 to 30):(10 to 20):(8 to 15);
[0008] Preferably, the mass ratio of the main chain monomer unit to the side chain monomer unit is (25 to 35):(35 to 55);
[0009] Preferably, the mass ratio of the alkenylamide, alkenyl sulfonate and phenolic compound is (15 to 25):(10 to 15):(10 to 15).
[0010] In one specific embodiment, the modified starch is at least one selected from pregelatinized starch, carboxymethyl starch, cationic starch, oxidized starch, esterified starch, cross-linked starch, and composite modified starch; and / or
[0011] The alkenylamide is at least one selected from N,N-dimethylacrylamide, N,N-diethylacrylamide, N-vinylacetamide, acrylamide, and N-vinylmethylacetamide; and / or
[0012] The alkenyl sulfonate is at least one selected from styrene sulfonate (e.g., sodium styrene sulfonate), dodecylenebenzene sulfonate (e.g., sodium dodecylenebenzene sulfonate), dodecylene sulfonate (e.g., sodium dodecylene sulfonate), and acetylammonosulfonate (e.g., sodium acetylammonosulfonate); and / or
[0013] The phenolic compound is at least one selected from phenol, 2-nitrophenol, 4-nitrophenol, 2-chlorophenol, 4-chlorophenol, 4-chloro-3-methylphenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol.
[0014] Preferably, the modified starch is at least one of cationic starch (e.g., quaternary ammonium cationic starch), cross-linked starch (e.g., epichlorohydrin cross-linked starch), and carboxymethyl starch;
[0015] Preferably, the alkenylamide is at least one selected from N,N-dimethylacrylamide, N-vinylacetamide, acrylamide, and N-vinylmethylacetamide;
[0016] Preferably, the alkenyl sulfonate is at least one of styrene sulfonate (e.g., sodium styrene sulfonate) and ethyl-acrylamidosulfonate (e.g., sodium ethyl-acrylamidosulfonate);
[0017] Preferably, the phenolic compound is at least one selected from 2-nitrophenol, 4-nitrophenol, 4-chloro-3-methylphenol, and 2,4-dichlorophenol.
[0018] The second aspect of the present invention provides a method for preparing the polymer described in the first aspect of the present invention, which includes the following steps:
[0019] 1) Mix water, the main chain monomer corresponding to the main chain monomer unit, and the side chain monomer corresponding to the side chain monomer unit; adjust the pH value to obtain a monomer solution;
[0020] 2) An initiator is added dropwise to the monomer solution to remove oxygen, and the reaction yields the polymer.
[0021] In one specific embodiment, the water is considered to be 100% by mass, and the main-chain monomers account for 15% to 35% of the water by mass; and / or
[0022] The mass ratio of the main chain monomer to the side chain monomer is (15 to 35):(28 to 65); and / or
[0023] In the side-chain monomers, the mass ratio of alkenylamide, alkenyl sulfonate, and phenolic compound is (10 to 30):(10 to 20):(8 to 15); and / or
[0024] The mass ratio of the side-chain monomer to the initiator is 1:(0.1 to 0.3); and / or
[0025] The initiator is at least one selected from ammonium perchlorate, ammonium persulfate, sodium persulfate, potassium persulfate, azobisisobutyronitrile, and sodium bisulfite; and / or
[0026] In step 1), the pH value is adjusted using an inorganic base (e.g., sodium hydroxide and / or potassium hydroxide); and / or
[0027] The pH value is 5 to 8; and / or
[0028] The reaction temperature is 65 to 75°C; and / or
[0029] The reaction lasts for 3 to 6 hours;
[0030] Preferably, the water is considered to be 100% by mass, and the main chain monomer accounts for 25% to 35% of the water by mass.
[0031] Preferably, the mass ratio of the main chain monomer to the side chain monomer is (25 to 35):(35 to 55);
[0032] Preferably, in the side chain monomer, the mass ratio of alkenylamide, alkenyl sulfonate and phenolic compound is (15 to 25):(10 to 15):(10 to 15);
[0033] Preferably, the mass ratio of the side-chain monomer to the initiator is 1:(0.2 to 0.3);
[0034] Preferably, the initiator is at least one selected from ammonium persulfate, sodium persulfate, potassium persulfate, and sodium bisulfite;
[0035] Preferably, the pH value is 6.5 to 7.5;
[0036] Preferably, the reaction lasts for 4 to 5 hours.
[0037] The third invention provides a method for preparing a filtration loss reducing agent, which includes the following steps:
[0038] The polymer and nanomaterials are mixed, oxygen is removed, and the reaction yields the filtration loss reducer.
[0039] The polymer is either the polymer described in one of the present invention or a polymer prepared by the method described in another of the present invention.
[0040] In one specific embodiment, the mass ratio of the polymer to the nanomaterial is 1:(0.1 to 0.3); and / or
[0041] The nanomaterial is at least one selected from nano-silica, nano-calcium carbonate, nano-zinc oxide, nano-alumina, nano-titanium dioxide, and nano-montmorillonite; and / or
[0042] The particle size of the nanomaterial is 15 to 60 nm.
[0043] Preferably, the mass ratio of the polymer to the nanomaterial is 1:(0.15 to 0.25);
[0044] Preferably, the nanomaterial is at least one selected from nano-silica, nano-calcium carbonate, nano-zinc oxide, and nano-titanium dioxide;
[0045] Preferably, the particle size of the nanomaterial is 20 to 40 nm.
[0046] In one specific embodiment, the reaction temperature is 65 to 75°C; and / or
[0047] The reaction duration is 0.5 to 1.5 hours; and / or
[0048] The particle size of the filtration loss reducer is such that it passes through a 60-mesh sieve;
[0049] Preferably, the reaction time is 0.5 to 1 hour.
[0050] The fourth invention provides a filtration loss reducer prepared by the method described in the third invention.
[0051] The application of at least one of the polymers described in one of the present inventions, the polymers prepared by the method described in the second of the present invention, the filtration loss reducer prepared by the method described in the third of the present invention, and the filtration loss reducer described in the fourth of the present invention in reducing filtration loss, particularly as a filtration loss reducer for drilling fluids.
[0052] The beneficial effects of this invention are:
[0053] This invention addresses the problem that existing drilling filtration loss reducers often fail to simultaneously achieve both high temperature and salt resistance and environmental performance. It provides a polymer, its preparation method, and a filtration loss reducer containing the polymer. The polymer provided in this invention has a modified starch main chain that acts as a backbone. The raw materials are readily available, inexpensive, and environmentally friendly. The polymer formed by reacting modified starch with alkenylamide, alkenyl sulfonate, and phenolic compounds exhibits strong salt and high temperature resistance, significant protective effect in high-temperature and high-salt environments, and still possesses strong hydration capacity and salt resistance. The filtration loss reducer prepared from the polymer and nanomaterials using the preparation method provided in this invention possesses excellent salt and high temperature resistance while also exhibiting good environmental performance and excellent filtration loss reduction: it can withstand saturated brine; it can withstand temperatures up to 180℃; the pressure filtration loss in API after aging at 180℃ for 16 hours is ≤15mL; and the biodegradability ratio (BOD5 / COD) is [not specified]. Cr >10%, biotoxicity meets environmental protection requirements (EC) 50 With a concentration ≥30000mg / L, it can be used to construct high-performance, environmentally friendly water-based drilling fluid systems. Therefore, the filtration loss reducer further prepared from the polymer provided by this invention is suitable for industrial mass production and has good application effects in oil and gas drilling operations, with significantly enhanced filtration loss reduction performance compared to existing technologies. Attached Figure Description
[0054] Figure 1 The image shown is a physical picture of the filtration loss reducer prepared in Example 13 of this invention. Detailed Implementation
[0055] The present invention will be further described below with reference to the embodiments. However, the embodiments of the present invention are merely illustrative examples and should not be construed as limiting the present invention under any circumstances.
[0056] Carboxymethyl starch: purchased from Shandong Deshunyuan Petroleum Technology Co., Ltd., brand name SMR;
[0057] Pregelatinized starch: purchased from Hebei Yanxing Chemical Co., Ltd., brand name YXYC;
[0058] Quaternary ammonium cationic starch: purchased from Dongying Shida Innovation Technology Co., Ltd., brand name SDMS;
[0059] Epichlorohydrin crosslinked starch: purchased from Shandong Deshunyuan Petroleum Technology Co., Ltd., brand name LYS;
[0060] Oxidized starch: purchased from Zhucheng Xingmao Corn Development Co., Ltd., brand name XMOC;
[0061] Esterified starch: purchased from Dongying Shida Innovation Technology Co., Ltd., brand name SDES;
[0062] Compound modified starch: purchased from Shengli Oilfield Boyou Mud Technology Co., Ltd., brand name HTS.
[0063] Preparation of polymers
[0064] Example 1
[0065] Prepare the polymer according to the following steps:
[0066] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 45 parts by weight of carboxymethyl starch, 22.5 parts by weight of N,N-dimethylacrylamide, 15 parts by weight of sodium ethyl acrylamide sulfonate, and 15 parts by weight of 2-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 7.
[0067] 2) Raise the temperature of the reaction system to 65°C, stir at a stirring speed of 800 r / min, and simultaneously add 15.75 parts by mass of ammonium persulfate to the reaction system dropwise through a constant pressure funnel over a period of 0.5 h. Purge oxygen with nitrogen gas and react for 4 h at a stirring speed of 800 r / min to obtain the polymer.
[0068] Example 2
[0069] Prepare the polymer according to the following steps:
[0070] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 45 parts by weight of pregelatinized starch, 22.5 parts by weight of N,N-dimethylacrylamide, 15 parts by weight of sodium ethyl acrylamide sulfonate, and 15 parts by weight of 2-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 7.
[0071] 2) Raise the temperature of the reaction system to 65°C, stir at a stirring speed of 800 r / min, and simultaneously add 15.75 parts by mass of ammonium persulfate to the reaction system dropwise through a constant pressure funnel for 0.5 h; purge oxygen with nitrogen gas, and react at a stirring speed of 800 r / min for 4 h to obtain the polymer.
[0072] Example 3
[0073] Prepare the polymer according to the following steps:
[0074] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 45 parts by weight of carboxymethyl starch, 22.5 parts by weight of N,N-dimethylacrylamide, 15 parts by weight of sodium ethyl acrylamide sulfonate, and 15 parts by weight of 2-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 7.
[0075] 2) Raise the temperature of the reaction system to 65°C, stir at a stirring speed of 800 r / min, and simultaneously add 10.5 parts by mass of ammonium persulfate to the reaction system dropwise through a constant pressure funnel for 0.5 h. Purge oxygen with nitrogen gas and react for 4 h at a stirring speed of 800 r / min to obtain the polymer.
[0076] Example 4
[0077] Prepare the polymer according to the following steps:
[0078] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 45 parts by weight of carboxymethyl starch, 22.5 parts by weight of N-vinylacetamide, 15 parts by weight of sodium ethyl acrylamide sulfonate, and 15 parts by weight of 2-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 7.
[0079] 2) Raise the temperature of the reaction system to 65°C, stir at a stirring speed of 800 r / min, and simultaneously add 15.75 parts by mass of ammonium persulfate to the reaction system dropwise through a constant pressure funnel over a period of 0.5 h. Purge oxygen with nitrogen gas and react for 4 h at a stirring speed of 800 r / min to obtain the polymer.
[0080] Example 5
[0081] Prepare the polymer according to the following steps:
[0082] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 37.5 parts by weight of quaternary ammonium cationic starch, 17 parts by weight of acrylamide, 10.2 parts by weight of sodium styrene sulfonate, and 10.3 parts by weight of 4-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 6.5.
[0083] 2) Raise the temperature of the reaction system to 70°C, stir at a stirring speed of 800 r / min, and simultaneously add 9.38 parts by mass of sodium persulfate to the reaction system dropwise through a constant pressure funnel over a period of 0.5 h. Purge oxygen with nitrogen gas and react for 4.5 h at a stirring speed of 800 r / min to obtain the polymer.
[0084] Example 6
[0085] Prepare the polymer according to the following steps:
[0086] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 52.5 parts by weight of epichlorohydrin crosslinked starch, 52.5 parts by weight of N-vinylmethylacetamide, 31.5 parts by weight of sodium ethyl acrylamide sulfonate, and 31.5 parts by weight of 4-chloro-3-methylphenol in sequence. Stir at 500r / min for 20min to disperse the ingredients evenly, and add NaOH to adjust the pH to 7.5.
[0087] 2) Raise the temperature of the reaction system to 75°C, stir at a stirring speed of 800 r / min, and simultaneously add 28.9 parts by mass of potassium persulfate dropwise into the reaction system through a constant pressure funnel for 0.5 h. Purge oxygen with nitrogen gas and react at a stirring speed of 800 r / min for 4.5 h to obtain the polymer.
[0088] Example 7
[0089] Prepare the polymer according to the following steps:
[0090] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 52.5 parts by weight of carboxymethyl starch, 58 parts by weight of acrylamide, 23 parts by weight of sodium styrene sulfonate, and 34.5 parts by weight of 2,4-dichlorophenol in sequence. Stir at 500r / min for 20min to disperse the flask evenly. Add NaOH to adjust the pH to 6.5.
[0091] 2) Raise the temperature of the reaction system to 70°C, stir at a stirring speed of 800 r / min, and simultaneously add 23.1 parts by mass of sodium bisulfite dropwise into the reaction system through a constant pressure funnel for 0.5 h; purge oxygen with nitrogen gas, and react for 5 h at a stirring speed of 800 r / min to obtain the polymer.
[0092] Example 8
[0093] Prepare the polymer according to the following steps:
[0094] 1) In a 250ml four-necked flask equipped with a reflux device, a stirrer, and a nitrogen purging tube, add 150 parts by weight of deionized water, 30 parts by weight of carboxymethyl starch, 15 parts by weight of N,N-dimethylacrylamide, 10 parts by weight of sodium ethyl acrylamide sulfonate, and 10 parts by weight of 2-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 7.
[0095] 2) Raise the temperature of the reaction system to 65°C, stir at a stirring speed of 800 r / min, and simultaneously add 10.5 parts by mass of ammonium persulfate to the reaction system dropwise through a constant pressure funnel for 0.5 h; purge oxygen with nitrogen gas, and react at a stirring speed of 800 r / min for 4 h to obtain the polymer.
[0096] Example 9
[0097] Prepare the polymer according to the following steps:
[0098] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 30 parts by weight of oxidized starch, 8.6 parts by weight of N,N-diethylacrylamide, 8.6 parts by weight of sodium dodecylenebenzenesulfonate, and 6.8 parts by weight of 2-chlorophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add KOH to adjust the pH to 5.
[0099] 2) Raise the temperature of the reaction system to 70°C, stir at a stirring speed of 800 r / min, and simultaneously add 2.4 parts by mass of azobisisobutyronitrile to the reaction system dropwise through a constant pressure funnel for 0.5 h. Purge oxygen with nitrogen gas and react for 3 h at a stirring speed of 800 r / min to obtain the polymer.
[0100] Example 10
[0101] Prepare the polymer according to the following steps:
[0102] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 22.5 parts by weight of esterified starch, 30 parts by weight of N,N-diethylacrylamide, 20 parts by weight of sodium dodecylenebenzenesulfonate, and 8 parts by weight of 4-chlorophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 5.
[0103] 2) Raise the temperature of the reaction system to 75°C, stir at a stirring speed of 800 r / min, and simultaneously add 8.7 parts by mass of ammonium perchlorate dropwise into the reaction system through a constant pressure funnel over a period of 0.5 h. Purge oxygen with nitrogen gas and obtain the polymer in 3.5 h at a stirring speed of 800 r / min.
[0104] Example 11
[0105] Prepare the polymer according to the following steps:
[0106] 1) Add 150 parts by weight of deionized water to a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube. Then add 30 parts by weight of composite modified starch, 45 parts by weight of N,N-diethylacrylamide, 30 parts by weight of sodium dodecylene sulfonate, and 22.5 parts by weight of 2,4,6-trichlorophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly. Add NaOH to adjust the pH to 8.
[0107] 2) Raise the temperature of the reaction system to 75°C, stir at a stirring speed of 800 r / min, and simultaneously add 9.75 parts by mass of azobisisobutyronitrile to the reaction system dropwise through a constant pressure funnel for 0.5 h. Purge oxygen with nitrogen gas and react at a stirring speed of 800 r / min for 5.5 h to obtain the polymer.
[0108] Example 12
[0109] Prepare the polymer according to the following steps:
[0110] 1) Add 150 parts by weight of deionized water to a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube. Then add 30 parts by weight of oxidized starch, 43.3 parts by weight of N,N-diethylacrylamide, 57.8 parts by weight of sodium dodecylene sulfonate, and 28.9 parts by weight of phenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly. Add NaOH to adjust the pH to 8.
[0111] 2) Raise the temperature of the reaction system to 75°C, stir at a stirring speed of 800 r / min, and simultaneously add 19.5 parts by mass of ammonium perchlorate dropwise into the reaction system through a constant pressure funnel for 0.5 h. Purge oxygen with nitrogen gas and react for 6 h at a stirring speed of 800 r / min to obtain the polymer.
[0112] Preparation of filtration loss reducer
[0113] Example 13
[0114] Prepare the filtration loss reducer according to the following steps:
[0115] 1) Mix 50 parts by mass of the polymer prepared in Example 1 with 10 parts by mass of nano-silica with a median particle size of 25 nm, and react with nitrogen to remove oxygen for 0.5 h under stirring at 65 °C and 800 r / min to obtain the filtration loss reducer.
[0116] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0117] Example 14
[0118] Prepare the filtration loss reducer according to the following steps:
[0119] 1) Mix 50 parts by mass of the polymer prepared in Example 2 with 10 parts by mass of nano-silica with a median particle size of 25 nm, and react with nitrogen to remove oxygen for 0.5 h under stirring at 65 °C and 800 r / min to obtain the filtration loss reducer.
[0120] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0121] Example 15
[0122] Prepare the filtration loss reducer according to the following steps:
[0123] 1) Mix 50 parts by weight of the polymer prepared in Example 1 with 10 parts by weight of nano-calcium carbonate with a median particle size of 25 nm, and react with nitrogen to remove oxygen for 0.5 h under stirring at 65 °C and 800 r / min to obtain the filtration loss reducer.
[0124] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0125] Example 16
[0126] Prepare the filtration loss reducer according to the following steps:
[0127] 1) Mix 50 parts by mass of the polymer prepared in Example 3 with 10 parts by mass of nano-silica with a median particle size of 25 nm, and react with nitrogen to remove oxygen for 0.5 h under stirring at 65 °C and 800 r / min to obtain the filtration loss reducer.
[0128] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0129] Example 17
[0130] Prepare the filtration loss reducer according to the following steps:
[0131] 1) Mix 50 parts by mass of the polymer obtained in Example 4 with 10 parts by mass of nano-silica with a median particle size of 25 nm, and react with nitrogen to remove oxygen for 0.5 h under stirring at 65 °C and 800 r / min to obtain the filtration loss reducer.
[0132] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0133] Example 18
[0134] Prepare the filtration loss reducer according to the following steps:
[0135] 1) Mix 50 parts by mass of the polymer obtained in Example 5 with 7.5 parts by mass of nano zinc oxide with a median particle size of 20 nm, and react with nitrogen to remove oxygen for 0.75 h under stirring at 70 °C and 800 r / min to obtain the filtration loss reducer.
[0136] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0137] Example 19
[0138] Prepare the filtration loss reducer according to the following steps:
[0139] 1) Mix 50 parts by weight of the polymer prepared in Example 6 with 7.5 parts by weight of nano-alumina with a median particle size of 30 nm, and react with nitrogen to remove oxygen for 0.75 h under stirring at 75 °C and 800 r / min to obtain the filtration loss reducer.
[0140] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0141] Example 20
[0142] Prepare the filtration loss reducer according to the following steps:
[0143] 1) Mix 50 parts by mass of the polymer prepared in Example 7 with 12.5 parts by mass of nano-titanium dioxide with a median particle size of 40 nm, and react with nitrogen to remove oxygen for 1 h under stirring at 70°C and 800 r / min to obtain the filtration loss reducer.
[0144] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0145] Example 21
[0146] Prepare the filtration loss reducer according to the following steps:
[0147] 1) Mix 50 parts by mass of the polymer prepared in Example 8 with 10 parts by mass of nano-silica with a median particle size of 25 nm, and react with nitrogen to remove oxygen for 0.5 h under stirring at 65 °C and 800 r / min to obtain the filtration loss reducer.
[0148] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0149] Example 22
[0150] Prepare the filtration loss reducer according to the following steps:
[0151] 1) Mix 50 parts by mass of the polymer prepared in Example 9 with 5 parts by mass of nano-montmorillonite with a median particle size of 15 nm, and react with nitrogen to remove oxygen for 1.2 h under stirring at 70 °C and 800 r / min to obtain the filtration loss reducer;
[0152] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0153] Example 23
[0154] Prepare the filtration loss reducer according to the following steps:
[0155] 1) Mix 50 parts by mass of the polymer prepared in Example 10 with 6 parts by mass of nano-alumina with a median particle size of 45 nm, and react with nitrogen to remove oxygen for 1.2 h under stirring at 75 °C and 800 r / min to obtain the filtration loss reducer.
[0156] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0157] Example 24
[0158] Prepare the filtration loss reducer according to the following steps:
[0159] 1) Mix 50 parts by weight of the polymer prepared in Example 11 with 15 parts by weight of nano-alumina with a median particle size of 55 nm, and react with nitrogen to remove oxygen for 1.5 h under stirring at 75 °C and 800 r / min to obtain the filtration loss reducer.
[0160] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0161] Example 25
[0162] Prepare the filtration loss reducer according to the following steps:
[0163] 1) Mix 50 parts by weight of the polymer prepared in Example 12 with 15 parts by weight of nano-alumina with a median particle size of 60 nm, and react with nitrogen to remove oxygen for 1.5 h under stirring at 75 °C and 800 r / min to obtain the filtration loss reducer.
[0164] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0165] Example 26
[0166] Preparation of filtration loss reducing agent:
[0167] The nano-silica with a median particle size of 25 nm in Example 13 was removed, and everything else was the same as in Example 13.
[0168] Comparative Example 1
[0169] Preparation of polymers:
[0170] The 2-nitrophenol in Example 1 was replaced with an equal mass of deionized water, and everything else was the same as in Example 1.
[0171] Comparative Example 2
[0172] Polymer preparation:
[0173] The step of adjusting the pH value in Example 1 is deleted, and everything else is the same as in Example 1.
[0174] Comparative Example 3
[0175] Prepare the polymer according to the following steps:
[0176] 1) In a 250ml four-necked flask equipped with a reflux device, stirrer, and nitrogen purging tube, add 150 parts by weight of deionized water, 75 parts by weight of carboxymethyl starch, 5 parts by weight of N,N-dimethylacrylamide, 25 parts by weight of sodium ethyl acrylamide sulfonate, and 22 parts by weight of 2-nitrophenol in sequence. Stir at 500r / min for 20min to disperse the mixture evenly, and add NaOH to adjust the pH to 9.
[0177] 2) Raise the temperature of the reaction system to 100℃, stir at a stirring speed of 800r / min, and simultaneously add 25 parts by mass of ammonium persulfate to the reaction system dropwise through a constant pressure funnel for 0.5h. Purge oxygen with nitrogen gas and react for 7h at a stirring speed of 800r / min to obtain the polymer.
[0178] Comparative Example 4
[0179] Preparation of filtration loss reducing agent:
[0180] The polymer in Example 13 was replaced with the polymer prepared in Comparative Example 1, and everything else was the same as in Example 13.
[0181] Comparative Example 5
[0182] Preparation of filtration loss reducing agent:
[0183] The polymer in Example 13 was replaced with the polymer prepared in Comparative Example 2, and everything else was the same as in Example 13.
[0184] Comparative Example 6
[0185] Prepare the filtration loss reducer according to the following steps:
[0186] 1) Mix 50 parts by mass of the polymer prepared in Comparative Example 3 with 25 parts by mass of nano-silica with a median particle size of 25 nm, and react with nitrogen gas to remove oxygen for 2 h under stirring at 100 °C and 800 r / min to obtain the filtration loss reducer.
[0187] 2) After the filtration loss reducing agent is extracted and purified with acetone, it is sheared, granulated, vacuum dried, pulverized, and ground to obtain the filtration loss reducing agent in powder form that passes through a 60-mesh sieve.
[0188] Comparative Example 7
[0189] The temperature-resistant and salt-resistant filtration loss reducer produced by Jiujiang Lanzhuo New Material Technology Co., Ltd.
[0190] Experimental Evaluation
[0191] 1. Evaluation of Filtration Loss Reduction Performance
[0192] The filtration loss reduction performance of the filtration loss reducing agents in Examples 13 to 26 and Comparative Examples 4 to 7 was evaluated. The experimental slurry preparation methods are as follows:
[0193] 1) Preparation of prehydrated bentonite slurry: Mix 100 parts by weight of water with 4 parts by weight of bentonite evenly to obtain prehydrated bentonite slurry;
[0194] 2) Preparation of experimental slurry: Add 2% of the filtration loss reducers of Examples 13 to 26 and Comparative Examples 4 to 7 (based on the mass of the prehydrated bentonite slurry in step 1) respectively, stir at 10000 r / min for 60 min, then add 4% of the sodium chloride (based on the mass of the prehydrated bentonite slurry), stir at 10000 r / min for 20 min to obtain 18 experimental slurries.
[0195] The filtration loss reduction performance of 18 groups of experimental slurries before and after hot rolling at 180℃ was tested according to the "API filtration loss test" method specified in standard GB / T 16783.1-2014.
[0196] The filtration loss (static filtration loss) in the API of 18 experimental slurries was tested, and the data are shown in Table 1:
[0197] Table 1. Filtration Loss in API Medium Pressure
[0198]
[0199] (Continued from Table 1)
[0200]
[0201] 2. Environmental performance evaluation
[0202] The environmental performance of the filtration loss reducing agents of Examples 13 to 26 and Comparative Examples 4 to 7 was tested using the following methods:
[0203] 1) Biodegradability test: The biodegradability of the filtration loss reducers in Examples 13 to 26 and Comparative Examples 4 to 7 was tested using an intelligent BOD analyzer (SN-870H type) and a COD analyzer (LH-T725 type).
[0204] 2) Biotoxicity testing: A biotoxicity testing instrument ( The biotoxicity of the filtration loss reducers in Examples 13 to 26 and Comparative Examples 4 to 7 was tested using Model 500.
[0205] The specific test data is shown in Table 2:
[0206] Table 2. Biodegradability and Biotoxicity
[0207]
[0208] (Continued from Table 2)
[0209]
[0210] While the present invention has been described with reference to specific embodiments, those skilled in the art will understand that various changes can be made without departing from the true spirit and scope of the invention. Furthermore, numerous modifications can be made to the subject, spirit, and scope of the invention to suit specific situations, materials, material compositions, and methods. All such modifications are included within the scope of the claims of the present invention.
Claims
1. A method for preparing a filtration loss reducing agent, comprising the following steps: The polymer and nanomaterials are mixed, oxygen is removed, and the reaction yields the filtration loss reducer. The polymer comprises main chain monomer units and side chain monomer units; The main chain monomer unit is modified starch, and the side chain monomer unit is alkenylamide, alkenyl sulfonate, and phenolic compound; The mass ratio of the main chain monomer unit to the side chain monomer unit is (15 to 35):(28 to 65); The mass ratio of the alkenylamide, alkenyl sulfonate, and phenolic compound is (10 to 30):(10 to 20):(8 to 15); The mass ratio of the polymer to the nanomaterial is 1:(0.1 to 0.3); The filtration loss reducer is temperature resistant up to 180℃, and after aging at 180℃ for 16 hours, the filtration loss in API is ≤15mL, with a biodegradability value of BOD5 / COD. Cr >10%, biotoxicity meets environmental protection requirements (EC) 50 ≥30000 mg / L.
2. The method according to claim 1, characterized in that, The mass ratio of the main chain monomer unit to the side chain monomer unit is (25 to 35):(35 to 55); The mass ratio of the alkenylamide, alkenyl sulfonate, and phenolic compound is (15 to 25):(10 to 15):(10 to 15).
3. The method according to claim 1, characterized in that, The modified starch is at least one of pregelatinized starch, carboxymethyl starch, cationic starch, oxidized starch, esterified starch, cross-linked starch, and composite modified starch; and / or The alkenylamide is at least one selected from N,N-dimethylacrylamide, N,N-diethylacrylamide, N-vinylacetamide, acrylamide, and N-vinylmethylacetamide; and / or The alkenyl sulfonate is at least one selected from styrene sulfonate, sodium dodecylenebenzene sulfonate, and sodium dodecylene sulfonate; and / or The phenolic compound is at least one selected from phenol, 2-nitrophenol, 4-nitrophenol, 2-chlorophenol, 4-chlorophenol, 4-chloro-3-methylphenol, 2,4-dichlorophenol, and 2,4,6-trichlorophenol.
4. The method according to any one of claims 1 to 3, characterized in that, The polymer is prepared according to the following steps: 1) Mix water, the main chain monomer corresponding to the main chain monomer unit, and the side chain monomer corresponding to the side chain monomer unit; adjust the pH value to obtain a monomer solution; 2) An initiator is added dropwise to the monomer solution to remove oxygen, and the reaction yields the polymer.
5. The method according to claim 4, characterized in that, The water is taken as 100% by mass, and the main-chain monomers account for 15% to 35% of the water by mass; and / or The mass ratio of the main chain monomer to the side chain monomer is (15 to 35):(28 to 65); and / or In the side-chain monomers, the mass ratio of alkenylamide, alkenyl sulfonate, and phenolic compound is (10 to 30):(10 to 20):(8 to 15); and / or The mass ratio of the side-chain monomer to the initiator is 1:(0.1 to 0.3); and / or The initiator is at least one selected from ammonium perchlorate, ammonium persulfate, sodium persulfate, potassium persulfate, azobisisobutyronitrile, and sodium bisulfite; and / or In step 1), the pH value is adjusted using an inorganic base; and / or The pH value is 5 to 8; and / or The reaction temperature in step 2) is 65 to 75°C; and / or The reaction time in step 2) is 3 to 6 hours.
6. The method according to claim 5, characterized in that, The water is considered to be 100% by mass, and the main chain monomers account for 25% to 35% of the water by mass. The mass ratio of the main chain monomer to the side chain monomer is (25 to 35):(35 to 55); In the side chain monomer, the mass ratio of alkenylamide, alkenyl sulfonate and phenolic compound is (15 to 25):(10 to 15):(10 to 15); The mass ratio of the side-chain monomer to the initiator is 1:(0.2 to 0.3); The pH value is 6.5 to 7.5; The reaction time in step 2) is 4 to 5 hours.
7. The method according to claim 1, characterized in that, The nanomaterial is at least one selected from nano-silica, nano-calcium carbonate, nano-zinc oxide, nano-alumina, nano-titanium dioxide, and nano-montmorillonite; and / or The particle size of the nanomaterial is 15 to 60 nm.
8. The method according to claim 1, characterized in that, The reaction temperature is 65 to 75°C; and / or The reaction lasts for 0.5 to 1.5 hours; and / or The particle size of the filtration loss reducer is such that it passes through a 60-mesh sieve.
9. A filtration loss reducer prepared by any one of claims 1 to 8.
10. The use of the fluid loss reducer prepared by any one of claims 1 to 8 or the fluid loss reducer of claim 9 as a fluid loss reducer for drilling fluids.
Citation Information
Patent Citations
High temperature resistant modified starch filtration reducing agent and preparation method thereof
CN103396515A
Fluid loss additive for drilling fluid
CN104371675A